Abu Syubhah Thoughts on Criticism of the Hadith of Abu Rayyah and Muhammad Amin - Ulfa Rahmadita (Yayasan Insan Mulia Bima, 2024)
This article discusses the hadith thoughts of people who deny the sunnah. People who adhere to the ideology of denying al-Sunnah consider that the hadith are mere lies originating from the Prophet Muhammad Saw, and the Koran is the only Islamic teaching that Muslims must adhere to as their guide to life. Among those who deny the Sunnah from modern circles are Abu Rayyah and Ahmad Amin. This article aims to examine the thoughts of Abu Rayyah and Ahmad Amin regarding the hadith and sunnah of the Prophet Saw. This research uses library research which explains the thoughts of people who disbelieve the Sunnah of the Prophet Saw. The results of this study if the thoughts of Abu Rayyah and Ahmad Amin contained several accusations against the hadith of the Prophet Saw. He believes that the Sunnah has a higher position than the Hadith. This accusation is not only related to the hadith but also to the narrators of the hadith such as Abu Hurairah. Therefore, to refute the accusations of Abu Rayyah and Ahmad Amin, a defense came from Muhammad bin Muhammad Abi Syahbah regarding these accusations.